Twenty-First Century Populism The Spectre of Western European Democracy - Albertazzi, D.; Albertazzi, D.; McDonnell, D.; McDonnell, D. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
Twenty-First Century Populism analyses the phenomenon of sustained populist growth in Western Europe by looking at the conditions facilitating populism in specific national contexts and then examining populist fortunes in those countries. The chapters are written by country experts and political scientists from across the continent.